2012
DOI: 10.1144/sp363.14
|View full text |Cite
|
Sign up to set email alerts
|

Some consequences of mechanical stratification in basin-scale numerical models of passive-margin salt tectonics

Abstract: Two-dimensional plane-strain numerical experiments illustrate the effects of variable evaporite viscosity and embedded frictional-plastic sediment layers on the style of salt flow and associated deformation of the sedimentary overburden. Evaporite viscosity exerts a first-order control on the salt flow rate and the style of overburden deformation. Nearly complete evacuation of low-viscosity salt occurs beneath expulsion basins, whereas significant salt is trapped when viscosity is high. Embedded frictional-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 38 publications
5
51
0
Order By: Relevance
“…For simplicity and general applicability, we do not simulate syn‐kinematic sedimentation and assume a homogeneous overburden underlain by a salt interval with densities of, respectively, 2.3 g cm −3 and 2.16 g cm −3 . These values concur with nature and previous physical and numerical analogues (Albertz & Ings, ; Dooley et al, , ; Gemmer et al, ; Gradmann & Beaumont, ; Ings & Shimeld, ). The maximum and minimum salt thicknesses for each model are 2.1 km and 750 m respectively, due to gradual thinning of the salt across pre‐salt structural highs.…”
Section: Methods and Models Designsupporting
confidence: 90%
“…For simplicity and general applicability, we do not simulate syn‐kinematic sedimentation and assume a homogeneous overburden underlain by a salt interval with densities of, respectively, 2.3 g cm −3 and 2.16 g cm −3 . These values concur with nature and previous physical and numerical analogues (Albertz & Ings, ; Dooley et al, , ; Gemmer et al, ; Gradmann & Beaumont, ; Ings & Shimeld, ). The maximum and minimum salt thicknesses for each model are 2.1 km and 750 m respectively, due to gradual thinning of the salt across pre‐salt structural highs.…”
Section: Methods and Models Designsupporting
confidence: 90%
“…8A, B). This finding is in agreement with other modelling studies, which showed that the salt viscosity exerts a fundamental control on the evolution of salt structures (Cohen and Hardy, 1996;Gemmer et al, 2004;Albertz and Ings, 2012). In our models we assumed a linear viscous behaviour of the salt.…”
Section: Salt Viscositysupporting
confidence: 91%
“…b Kopf (1967 1*10 18 Pa*s, which reflects the range of natural variations in salt viscosity (Van Keken et al, 1993;Weijermars et al, 1993). Such values were also applied in several other numerical simulations of salt tectonics (e.g., Gemmer et al, 2004;Albertz and Ings, 2012). However, the viscosity of natural salt will broadly vary depending on salt mineralogy, grain size, water contents and temperature (Van Keken et al, 1993;Weijermars et al, 1993).…”
Section: Model Geometry and Parametersmentioning
confidence: 99%
“…Similarly, the Aptian layered evaporite sequence of offshore Brazil contains little to no nonevaporite lithologies, but contains mostly halite with varying amounts of anhydrite, carnallite and other evaporite minerals (e.g., Karner, 2000;Meisling et al, 2001;Gamboa et al, 2008;Fiduk and Rowan, 2012). Despite these differences in composition and, thus, the average viscosity of the salt layer, which might be expected to influence the deformation (e.g., Albertz and Ings, 2012;Goteti et al, 2013), the Callanna Group appears to have mobilized in a similar fashion to the GOM and South Atlantic evaporites. However, the nature of the Callanna Group breccia and the similarity of its clasts to minibasin lithologies in terms of composition may explain in part the apparent absence of slumped material (rubble zone).…”
Section: Discussionmentioning
confidence: 99%